Molecular Identification and Management of Rhizoctonia Fragariae the Pathogen of Black Root Rot of Strawberry Plant - Aziz, Brwa A.; Marzani, Qasim A. (Science Journal of University of Zakho, 2017)
Strawberry plants are susceptible to a large number of pests and diseases and this can affect the quality and yield value of the fruit. Black root rot is an important disease of strawberry caused by a complex of fungi including Rhizoctonia. The most recognizable species of Rhizoctonia are R. solani and R. fragariae which are multinucleate and binucleate species, respectively. This work is aimed to isolate, identify and control the strawberry root rot caused by R. fragariae. Infected strawberry samples were collected from Erbil, Slemani, Duhok and Garmiyan Provinces. The identification of isolated fungi was achieved by using traditional methods along with molecular methods using polymerase chain reaction (PCR). In the later method, specific primers were designed and used to identify Rhizoctonia species. Several disease management options, including biological by using two species of Trichoderma, and chemical methods using Pristine fungicide, were also investigated. Sampling of strawberry plants revealed that the disease is prevalent in Kurdistan region and the isolated fungi, R. solani, Rhizoctonia sp., and R. fragariae, were pathogens of the disease causing crown and root rot of strawberry. PCR amplification was confirmed the identification of the species of Rhizoctonia. The results of control methods revealed that the most effective treatments were achieved using the fungicide followed by the use of the combination of T. harzianum and T. viride.
Keywords: Strawberry; Rhizoctonia fragariae; black root rot; PCR